STRATEGY TO PREVENT MASSIVE RECRUITMENT OF THE TERRORIST ORGANIZATIONS IN INDONESIA DURING THE COVID-19 PANDEMIC - Gia Ayu Fita; Stanislaus Riyanta (The Republic of Indonesia Defense University, 2022)
During the Covid-19 pandemic, the movement of the terrorist groups or the radical groups, which should have been